Lower running Performance and exacerbated fatigue in soccer played at 1600 m - Garvican, L. A.; Hammond, K.; Varley, M. C.; Gore, C. J.; Billaut, F.; Aughey, R. J. (International Journal of Sports Physiology and Performance, 2014)
Purpose: This study investigated the decrement in running performance of elite soccer players competing at low altitude and time course for abatement of these decrements. Methods: Twenty elite youth soccer players had their activity profile, in a sea-level (SL) and 2 altitude (Alt, 1600 m, d 4, and d 6) matches, measured with a global positioning system. Measures expressed in meters per minute of match time were total distance, low- and high-velocity running (LoVR, 0.01-4.16 m/s; HiVR, 4.17-10.0 m/s), and frequency of maximal accelerations (>2.78 m/s2). The peak and subsequent stanza for each measure were identified and a transient fatigue index calculated. Mean heart rate (HR) during the final minute of a submaximal running task (5 min, 11 km/h) was recorded at SL and for 10 d at Alt. Differences were determined between SL and Alt using percentage change and effect-size (ES) statistic with 90% confidence intervals. Results: Mean HR almost certainly increased on d 1 (5.4%, ES 1.01 ± 0.35) and remained probably elevated on both d 2 (ES 0.42 ± 0.31) and d3 (ES 0.30 ± 0.25), returning to baseline at d 5. Total distance was almost certainly lower than SL (ES -0.76 ± 0.37) at d 4 and remained probably reduced on d 6 (ES -0.42 ± 0.36). HiVR probably decreased at d 4 vs SL (-0.47 ± 0.59), with no clear effect of altitude at d 6 (-0.08 ± 0.41). Transient fatigue in matches was evident at SL and Alt, with a possibly greater decrement at Alt. Conclusion: Despite some physiological adaptation, match running performance of youth soccer players is compromised for at least 6 d at low altitude.